"The Glory ofGod Gives Life": Unmasking Subjugation for a Post-Colonial Missionary Ecclesiology in Canada - Fensham, Charles James (Toronto journal of theology, 2006)
Those who define what is acceptable within churches most often operate from the point of view of the dominant within the church subculture. Those who are different find themselves defined by those who dominate, control, exercise power and set the agenda. The dominated often seek to join dominance and to suppress their difference. This process is pernicious because it appears benign and because it never requires the dominant to reveal or examine assumptions. It reflects the process of one-way definition identified by Edward Said, another post-colonial theorist, in the relationship between the Western world and its perception of the Orient. There are many powerful challenges before churches in Canada in the twentyfirst century. I frame several issues here to propose the scope of post-colonial missionary ecclesiology. Challenges include external influences such as globalization, new technologies, environmental destruction, consumer capitalism and mass media; and internal struggles with hermeneutics, ethics, leadership and traditions of violence and domination.